Prevalence and diagnostic value of non-criteria antiphospholipid antibodies for antiphospholipid syndrome in Chinese patients - Li, Siting; Bai, Yina; Meng, Jingjing; Wang, Qian; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng; Zhao, Jiuliang; Hu, Chaojun (Frontiers in Immunology, 2023)
Background: The presence of antiphospholipid antibodies (aPLs) plays a pivotal role in the pathogenesis of antiphospholipid antibody syndrome (APS). This study aimed to examine the diagnostic value of a set of non‑criteria aPLs and their relevance with APS-related criteria and extra-criteria manifestations. Methods: From a prospectively constructed database, consecutive APS patients consisting of 114 primary APS (PAPS group), 54 with APS secondary to SLE (SAPS group), 9 seronegative APS (SNAPS), as well as 209 patients with systemic lupus erythematosus (SLE) and 88 healthy controls were included in this study. Levels of criteria aPLs, baseline information, and APS-related criteria and extra-criteria features were extracted from the database. Serum levels of non-criteria aPLs including aPC IgG/IgM, aPI IgG/IgM, aPE IgG/IgM/IgA, aPG IgG/IgM/IgA, anti-phosphatidic acid (aPA) IgG/IgM, aSM IgG/IgM, and aPS/PT IgG/IgM were analyzed with AESKULISA® ELISA Test Kits. Results: The addition of aPC IgG/M, aPI IgG/M, aPE IgG/M/A, aSM IgG/M, and aPA IgG/M to aCL or aβ2GPI IgG/M could significantly increase diagnostic sensitivity and accuracy. A significant difference between PAPS or SAPS and HC was presented in all non-criteria aPLs except for aSM IgM and aPG IgA. Eight out of nine SNAPS patients were positive for at least 1 aPL. Pregnancy morbidity was associated with aSM IgM (r = 0.22) and aSM IgG (r = 0.15). Pre-eclampsia or premature birth was associated with aSM IgG (r = 0.16), aPI IgG (r = 0.22), aPC IgG (r = 0.16), and aPG IgG (r = 0.18). Stroke was associated with aPI IgG (r = 0.2). The clinical association was also observed in DVT with aPS/PT IgG (r = 0.17). Valve lesion was positively associated with aSM IgM (Fisher test p = 0.039), APS nephropathy was associated with aPC IgG (OR 3.797), and livedo reticularis was associated with aPE IgM (OR 15.391). Conclusion: Additional detection of non-criteria aPLs including aPC IgG/M, aPE IgG/M/A, aPI IgG/M, aSM IgG/M, and aPA IgG/M could assist in APS diagnosis. The positivity of certain aPLs was statistically associated with both criteria and extra-criteria APS clinical manifestations.